2013 Proceedings IEEE INFOCOM 2013
DOI: 10.1109/infcom.2013.6566840
|View full text |Cite
|
Sign up to set email alerts
|

Prototyping energy harvesting active networked tags (EnHANTs)

Abstract: With the convergence of ultra-low-power communications and energy-harvesting technologies, networking selfsustainable ubiquitous devices is becoming feasible. Hence, we have been recently developing new devices, referred to as Energy Harvesting Active Networked Tags (EnHANTs). These small, flexible, and energetically self-reliant tags can be seen as a new class of devices in the domain between RFIDs and sensor networks. EnHANTs are made possible by advances in ultra-lowpower ultra-wideband (UWB) communications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 17 publications
0
39
0
Order By: Relevance
“…For this purpose we use a simple method where Figure 4 shows three average power requirements for a TelosB mote-class device under different duty cycles. These lines can be viewed to signify either different application requirements or a different class of devices [27,28].…”
Section: Supported Class Of Wsn Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose we use a simple method where Figure 4 shows three average power requirements for a TelosB mote-class device under different duty cycles. These lines can be viewed to signify either different application requirements or a different class of devices [27,28].…”
Section: Supported Class Of Wsn Applicationsmentioning
confidence: 99%
“…We, therefore, do not require a trade-off for lower capability platforms (like CRFID or EnHANTs [28]) which constrain the WSN applications we can support. Thus, all current WSN applications can simply focus on meeting the sensing requirements and request energy from our energy distribution system.…”
Section: Supported Class Of Wsn Applicationsmentioning
confidence: 99%
“…However, in many scenarios, a fixed power supply is not available, and even periodical battery replacement may not be a feasible option, for example, in large wireless sensor networks etc. In such situations, the use of energy harvesting (EH) for wireless communications appears appealing, or even essential by converting mechanical vibration into energy [11], by using solar panels [12], by utilizing thermoeletric generators [13], or by converting ambient radio power into energy [14]. EH provides a potentially infinite network operating time.…”
Section: Introduction 11 Motivationmentioning
confidence: 99%
“…Students demonstrated prototypes and the testbed at six conference demonstration sessions [11]- [16] and at over three dozen additional live on-site and offsite demonstrations. Students also contributed to publications describing the prototypes and the testbed [17], [18].To evaluate our learning activities, we conducted a survey among the students. Of the students who completed the survey, over 90% indicated that the project was rewarding and enriching, and 70% indicated that working on this project improved their ability to function on multidisciplinary teams more than any other activity in their academic career.…”
Section: Introductionmentioning
confidence: 99%
“…3: A timeline of the EnHANTs prototypes and testbed development, Phases I-VI. The milestones achieved during these phases were presented at conference demonstration sessions [11] (7 student coauthors), [12] (7 student coauthors), [14] (9 student coauthors), [13] (10 student coauthors), [15] (10 student coauthors), and [16] (8 student coauthors).…”
Section: Introductionmentioning
confidence: 99%